"Nuclear" and "nonnuclear" countries: Divergences on investment decisions in renewable energy sources. Issue 6 (2nd June 2016) - Romano, Antonio Angelo; Scandurra, Giuseppe
ABSTRACT: The aim of this study is to analyze the key factors of investment in renewable energy sources between countries with, or without, nuclear power plants. To address these issues, a dynamic panel analysis of the renewable investments in a sample of 32 countries is proposed. This study controls variables for socioeconomic, environmental, and policy characteristics in a time span between 1980 and 2008. Results demonstrate that investments in renewable sources present an inverse relationship with share of nuclear power generation in countries with nuclear power plants; however, in countries with power generation based on fossil fuel, investments in renewable sources depend on a number of factors.